(untitled) (The Review of Diabetic Studies, 2025)
Background Infection control in the 21st century builds on historical foundations from pioneers like Semmelweis, Lister, and Nightingale, confronting modern threats such as healthcare-associated infections (HAIs) affecting 136 million patients annually, antimicrobial resistance (AMR) causing over 1 million deaths yearly, and challenges from urbanization, globalization, and climate change.​ Methods This narrative review synthesizes 25 years of evidence, including landmark RCTs (e.g., REDUCE MRSA trial), meta-analyses, cohort studies, mathematical models, and GRADE/AMSTAR assessments of systematic reviews on core practices like hand hygiene, PPE, bundles, antimicrobial stewardship, and emerging technologies.​ Results Key interventions reduced HAIs by 40-60% (e.g., chlorhexidine bathing cut MRSA by 37%, bundles lowered CLABSIs/VAP by 50-60%), with compliance rising via WHO’s 5 Moments and digital tools; innovations like UV robots, RFID monitoring, and AI predictive analytics achieved 70-90% environmental reductions and outbreak forecasts; global HAI rates declined 50% since 2000, though gaps persist in LMICs and psychosocial barriers.​ Conclusions Multifaceted strategies integrating stewardship, technology (AI/nanotech), and policy yield substantial progress toward near-zero HAIs by 2030; future efforts must prioritize equity, sustained metrics, and interdisciplinary innovation to counter AMR amid evolving threats.​